2014
DOI: 10.2169/internalmedicine.53.1646
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide as a Potentially Useful Agent for Regulating Appetite in Diabetic Patients with Hypothalamic Hyperphagia and Obesity

Abstract: Hypothalamic hyperphagia and obesity are characterized by a lack of satiety and an abnormally high appetite that is difficult to control. We herein report the cases of two patients with hypothalamic hyperphagia and obesity with MRI-detectable hypothalamic lesions. These patients suffered from diabetes mellitus associated with an abnormal eating behavior and weight gain. Liraglutide was successfully used to treat their diabetes mellitus and suppress their abnormal appetites. Glucagon-like peptide-1 analogues, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…In the current study, obese animals showed glucose intolerance/insulin resistance, resistance to anorexigenic effect of leptin, elevated Bax/Bcl2 ratio, and microgliosis, indicating inflammation with stimulation of the pro-apoptosis in the ARC nucleus. We observed that liraglutide led to BM loss and carbohydrate metabolism improvement, confirming previous studies (1). The liraglutide treatment resulted in a leptin sensitivity enhancement, with reduction of microgliosis and stimulation of Bcl2, thus reducing the Bax/Bcl2 ratio.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, obese animals showed glucose intolerance/insulin resistance, resistance to anorexigenic effect of leptin, elevated Bax/Bcl2 ratio, and microgliosis, indicating inflammation with stimulation of the pro-apoptosis in the ARC nucleus. We observed that liraglutide led to BM loss and carbohydrate metabolism improvement, confirming previous studies (1). The liraglutide treatment resulted in a leptin sensitivity enhancement, with reduction of microgliosis and stimulation of Bcl2, thus reducing the Bax/Bcl2 ratio.…”
Section: Discussionsupporting
confidence: 91%
“…While weight loss was small, untreated patients continued to gain weight and our measured weight change may be an underestimation. Previous case reports showed greater than expected weight loss of 12.6 ± 7.1 kg in 11 patients with HO treated with GLP1RAs for ≥6 months . All but one patient had T2D, while our participants were treated for obesity.…”
Section: Discussionmentioning
confidence: 44%
“…GLP1RA may also increase energy expenditure . There are case reports of successful weight loss after treatment with GLP1RAs in patients with HO but no prospective pilot studies . The goal of this clinical trial was to investigate changes in body weight before and during treatment with exenatide.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, liraglutide has beneficial effects on waist circumference and numerous metabolic parameters including inflammatory markers, blood pressure (BP) and plasma lipids [3], thus improving the cardio-metabolic profile of patients with T2DM [4, 5]. Similar beneficial effects of liraglutide on metabolic parameters were also seen in obese individuals with prediabetes who were at high risk for progression to T2DM and the development of cardiovascular disease (CVD) [6], as well as in subjects who had hypothalamic pituitary injury followed by hyperphagia, in whom several features of the metabolic syndrome (MetS) were present [7]. …”
Section: Introductionmentioning
confidence: 99%